Feasibility of My Chicken Restaurant Business Development in Bulukumba Regency - Syam, Agus; Pertiwi, Wiwi; Halim, Nur; Jufri, Muhammad; Sudarmi, Sudarmi (Journal of Applied Business, Taxation and Economics Research, 2024)
This research aims to determine the feasibility of opening a new branch at the My Chicken restaurant on Jalan Poros Tanjung Bira, Bulukumba district. This research uses a qualitative approach. Data collection was carried out through observation, interviews and documentation techniques. The collected data is processed using data reduction steps, data presentation, and drawing conclusions/verification. The results of this research show that, based on the marketing aspect, the My Chicken restaurant is worthy of development, but must continue to carry out evaluations to continue developing new strategies in new locations. From a technical aspect, it is feasible to carry out, however there needs to be improvements in the technology and machines used in the My Chicken restaurant production process. From socio-economic and environmental aspects, it is feasible because it can provide positive benefits and the My Chicken restaurant will manage and be responsible for the waste produced